Bimetallic cobalt molybdenum carbide–cobalt composites as superior bifunctional oxygen electrocatalysts for Zn–air batteries. (December 2020) - Li, Yanqiang; Yin, Zehao; Cui, Ming; Chen, Siru; Ma, Tingli
Abstract: Designing composite material that contains high-active oxygen evolution reaction (OER) and oxygen reduction reaction (ORR) species is an effective strategy for synthesizing bifunctional electrocatalysts for Zn–air batteries. In this work, we first reported the preparation of the Co6 Mo6 C2 –Co@NC nanorod composite by using the Mo-polydopamine@ZIF-67 composite as the precursor. Because of the highly active Co6 Mo6 C2 for OER and the high-active Co for ORR, the Co6 Mo6 C2 –Co@NC exhibits superior OER activity, with a low overpotential of 268 mV at 10 mA cm −2, and high ORR performance. When used as bifunctional electrocatalysts for the Zn–air battery, the battery exhibits a high open-circuit voltage of 1.38 V and a specific capacity of 760 mA/h/g, as well as very high stability of up to 300 h with no obvious increase in charge–discharge voltage gap. Graphical abstract: A novel Co6 Mo6 C2 –Co@NC nanorod was developed as highly efficient bifunctional oxygen electrocatalysts for the Zn–air battery. Image 1 Highlights: Co6 Mo6 C2 –Co@NC nanorod composite was prepared by using the Mo-polydopamine@ZIF-67 composite as the precursor. The Co6 Mo6 C2  is demonstrated to be high active specie for oxygen evolution reaction. The Co6 Mo6 C2 –Co@NC composite exhibited a low OER overpotential of 268 mV at 10 mA cm −2 . The Co6 Mo6 C2 –Co@NC can be used for bifunctional electrocatalysts for the Zn–air battery.